The Doctorate in Clinical Laboratory Sciences: A New Curriculum to Enhance the Connection of the Laboratory to Health Care Providers. (6th August 2021) - Salazar, Jose H.; Zahner, Christopher J.; Freeman, Vicki S.; Laposata, Michael
This report discusses the need for a Doctorate in Clinical Laboratory Sciences program and describes a curriculum to train Doctorate in Clinical Laboratory Sciences students. The Doctorate in Clinical Laboratory Sciences program was developed to help reduce diagnostic errors in patient care by enhancing connections between the clinical laboratory and health care providers. Data are presented from program implementation in 2016 to 2017 academic year to 2019 to 2020 regarding the faculty and student demographics, program statistics (eg, admissions and attrition rates), and effectiveness. Perceptions of program effectiveness were obtained via surveys from 28 faculty physicians who supervised Doctorate in Clinical Laboratory Sciences students during clinical service rotations. Another survey assessed the preferred type of practice after graduation of 33 students. Over the 4-year period, the program had a 50% rate of admission and a 21.8% attrition rate. As of December 2020, 15 students graduated from the program. The majority (69%-82%) of physician faculty who completed the survey agreed that Doctorate in Clinical Laboratory Sciences students contributed positively at clinical rounds. Approximately two-thirds of students reported a preference to lead a Diagnostic Management Team or serve as an advanced practice provider in a Diagnostic Management Team with leadership provided by an MD/DO or PhD. This report provides useful information for other institutions that may want to establish similar Doctorate in Clinical Laboratory Sciences programs. Early data suggest that our program effectively trains doctoral-level advanced practice medical laboratory scientists, who may play an important role in improving patient safety by reducing diagnostic errors and providing value-based, optimal patient care.